Az Alkotmány egy vitatott bekezdése a 29/B. § (4) - Csink Lóránt (2005)
The method of electing a president is a significant feature of the connection of Parliament and the head-of-state, which links to the separation of public bodies and to the checks and balances system. This essay reconsiders the concerning Hungarian regulations first. It introduces the present procedure and calls the attention to the problem that the procedure has no absolute correspondence with the text of the Constitution, therefore the amendment of the said section seems to be necessary. Furthermore there are some other questions to deal with, for instance the problem of invalid votes and the secrecy of voting. In the second chapter the essay introduces the practice of the member states of the European Union, using a comparative method, in order to set examples to the Hungarian legislation. It can be clearly seen that the practices of the states differ in many ways. Beside the way of election, this chapter includes the conditions candidate presidents have to fulfil in the examined states. The last chapter questions if there's any link between the method of election and the form of government i.e. if direct election is a sign of presidency.
Keywords: Társadalomtudományok; Jogtudomány